2022
DOI: 10.1002/cam4.4765
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib as monotherapy versus combination therapy in Chinese patients with relapsed/refractory mantle cell lymphoma: A multicenter study

Abstract: Background: Ibrutinib has revolutionized the treatment of mantle cell lymphoma (MCL). Both ibrutinib monotherapy and ibrutinib-based combination therapy are important salvage options for patients with relapsed/refractory (R/R) MCL. The real-world efficacy and safety profile of the two strategies in Chinese patients with R/R MCL remain unclarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The treatment strategies reported in the first study resulted in a median PFS of 30.8 months, an ORR of 84.9%, and a CR of 43.4%, with a median follow-up of 20.5 months (for the overall study population). 24 Moreover, the efficacy of ibrutinib plus venetoclax in the second study was reported in terms of ORR and CR, which were 100% and 50%, respectively. 39…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The treatment strategies reported in the first study resulted in a median PFS of 30.8 months, an ORR of 84.9%, and a CR of 43.4%, with a median follow-up of 20.5 months (for the overall study population). 24 Moreover, the efficacy of ibrutinib plus venetoclax in the second study was reported in terms of ORR and CR, which were 100% and 50%, respectively. 39…”
Section: Resultsmentioning
confidence: 94%
“…Two studies analyzed the efficacy of ibrutinib in combination with other agents. The first one reported the outcomes of ibrutinib combined with several other agents (rituximab, lenalidomide, bortezomib, and/or bendamustine) in 53 patients (75.5% males, median age of 56 years), 24 of which 28.3%, 84.9%, 51.0%, and 54.7% had an ECOG score ≥2, a III–IV stage R/R-MCL, an intermediate-high sMIPI, and a Ki-67 index ≥30%, respectively. In addition, the percentages of patients with a previous auto-SCT, refractoriness to the most recent line of therapy, and blastoid histology were 9.4%, 47.2%, and 19.2%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of OS benefit across the years may be due to the fact that OS is influenced by subsequent regimens. Interestingly, the abovementioned OS benefit during the last 5 years for elderly patients could be due to the introduction of ibrutinib as a second-line regimen in Italy, unlike its limited use in Finland, where it is reimbursed as a fourth-line regimen [ 29 , 35 , 43 , 44 , 45 , 46 ]. The main limitation of our study is represented by the retrospective nature of the study and the reduced sample size, and this may explain why some classic prognostic factors, such as MIPI score and stage, did not affect PFS and OS in our cohort.…”
Section: Discussionmentioning
confidence: 99%